International expansion based on Uppsala model – cases of McDonald’s and Sfinks Poland - Hak, Andrzej; Grębosz, Magdalena (Wydawnictwa Politechniki Łódzkiej, 2016)
In the paper, the possibilities of entering foreign markets are described and the Uppsala model of internationalisation is analysed. The Uppsala model became one of the McDonald’s’ success factors, that can be multiplied by another food chains. In the paper, the internationalization process of the McDonald’s Corporation is presented to outline possible opportunities for Sfinks Polska as a developing and promising Polish business going abroad.
Keywords: model internacjonalizacji; model uppsalski; sieć restauracji; Sfinks; McDonald`s; model of internationalization; Uppsala model; restaurant chain